2001
DOI: 10.1074/jbc.m010660200
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Anaplastic Lymphoma Kinase as a Receptor for the Growth Factor Pleiotrophin

Abstract: Pleiotrophin (PTN) is a secreted growth factor that induces neurite outgrowth and is mitogenic for fibroblasts, epithelial, and endothelial cells. During tumor growth PTN can serve as an angiogenic factor and drive tumor invasion and metastasis. To identify a receptor for PTN, we panned a phage display human cDNA library against immobilized PTN protein as a bait. From this we isolated a phage insert that was homologous to an amino acid sequence stretch in the extracellular domain (ECD) of the orphan receptor t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
316
1
12

Year Published

2001
2001
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 350 publications
(335 citation statements)
references
References 46 publications
(64 reference statements)
6
316
1
12
Order By: Relevance
“…The phage display had revealed a fragment of the ALK extracellular domain (ECD) as the ligand-binding domain (LBD) and we found that PTN binds the recombinant ALK ECD protein as well as the receptor expressed in intact cells with dissociation constants (K d ) of approximately 30 pM ( ¼ 0.5 ng/ml). Also, antibodies raised to the ALK LBD as well as to PTN inhibited receptor binding of the ligand and signal transduction via ALK as well as biologic effects were observed at EC 50 values close to the K d of PTN binding to the ALK receptor (Stoica et al, 2001;Bowden et al, 2002;Powers et al, 2002). In support of this, recent work from the laboratory of Paul Mischel (Lu et al, 2005) using different glioblastoma cell line models also reported that ALK phosphorylation and signaling are induced by PTN.…”
Section: Introductionmentioning
confidence: 64%
See 3 more Smart Citations
“…The phage display had revealed a fragment of the ALK extracellular domain (ECD) as the ligand-binding domain (LBD) and we found that PTN binds the recombinant ALK ECD protein as well as the receptor expressed in intact cells with dissociation constants (K d ) of approximately 30 pM ( ¼ 0.5 ng/ml). Also, antibodies raised to the ALK LBD as well as to PTN inhibited receptor binding of the ligand and signal transduction via ALK as well as biologic effects were observed at EC 50 values close to the K d of PTN binding to the ALK receptor (Stoica et al, 2001;Bowden et al, 2002;Powers et al, 2002). In support of this, recent work from the laboratory of Paul Mischel (Lu et al, 2005) using different glioblastoma cell line models also reported that ALK phosphorylation and signaling are induced by PTN.…”
Section: Introductionmentioning
confidence: 64%
“…In the present paper, we analyze the contribution of IRS-1 to ALK signaling using the interleukin-3 (IL-3)-dependent, 32D murine hematopoietic cells that have no detectable ALK and IRS protein expression (Wang et al, 1993;Stoica et al, 2001;White, 2002). However, surprisingly, we found that 32D cells constitutively express the ALK ligand MK and upon transfection of ALK plus IRS-1, these cells grow and survive independent of IL-3 supplementation.…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations
“…Recently, ALK was proposed to be the physiological receptor of the 136 amino acid cytokine pleiotrophin (PTN, Ptn) [14]. However, these data were not reconciled with earlier studies that demonstrated that the Receptor Protein Tyrosine Phosphatase (RPTP) β/ζ is the functional receptor of PTN [15]; in those earlier studies, PTN was shown to inactivate RPTPβ/ζ and to increase tyrosine phosphorylation of the substrates of RPTPβ/ζ, which results from phosphorylation of these substrates by kinases that phosphorylate the same sites dephosphorylated by RPTPβ/ζ when cells are not stimulated by PTN.…”
Section: Introductionmentioning
confidence: 99%